The Emergence of Fascist Movement (1914 a 1930) (Historical Perspective) (Global Journal of Human-Social Science, 2016)
This study presents within historical perspective the Fascism movement emergence in Italy at the beginnings of 20th Century in a way to enable us realizing Fascism s movement the accompanying intolerance and violence prevailed in international relations at that time which were seemed as contemporary phenomenon at the beginning of 21st century under the control of unilateral global regime whereas the public or parliamentary role is Marginalized or even cancelled in making crucial decisions at the National State Level The foregoing works to foreshadowing the emergence of related intolerance and violence historical phenomena which can turn into a totalitarian dictatorship regime practicing violence via means similar to those practiced by Fascism Movement The main idea herein is based on historical experience s recovery as to Fascism movement in Italy development and impact thereof on its international relationships as well as followed tactics therein The foregoing offer us understanding in terms of contemporary new phenomenon which is still in its initial stage and thus contributing in increasing the historical awareness comprehend contemporary problems and impacts thereof
Keywords: Europe's contemporary history; fascism; fascist thinking and violence; international relations history; historical perspective